An Enhancer's Length and Composition Are Shaped by Its Regulatory Task - Li, Lily; Wunderlich, Zeba (Frontiers in Genetics, 2017)
Enhancers drive the gene expression patterns required for virtually every process in metazoans. We propose that enhancer length and transcription factor (TF) binding site composition—the number and identity of TF binding sites— reflect the complexity of the enhancer’s regulatory task. In development, we define regulatory task complexity as the number of fates specified in a set of cells at once. We hypothesize that enhancers with more complex regulatory tasks will be longer, with more, but less specific, TF binding sites. Larger numbers of binding sites can be arranged in more ways, allowing enhancers to drive many distinct expression patterns, and therefore cell fates, using a finite number of TF inputs. We compare ~100 enhancers patterning the more complex anterior-posterior axis and the simpler dorsal-ventral axis in Drosophila and find that the anterior-posterior enhancers are longer with more, but less specific binding sites than the dorsal-ventral enhancers. Using a set of ~3500 enhancers, we find enhancer length and TF binding site number again increase with increasing regulatory task complexity. Therefore, to be broadly applicable, computational tools to study enhancers must account for differences in regulatory task.